Development assessment model for middle manager in management and leadership in school - Jaafar, Junaidah; Said, Hamdan; Hashim, Abu Bakar (2008)
Nowdays we always wants good results from our educational area. We always concern about what will effects our outcomes. Leaders in school are the main factors that will stimulate the best condition for our expectation. Leaders face complex demands perhaps greater from the past. These conditions determine the best management and leadership education practices necessary for development of successful management and leadership behaviour. This research will focus the management and leadership for the middle manager in school. This research will construct a model for assessment the middle manager in school based. It may help to ensure the effectiveness and important rules of the middle manager.